Sustainable marketing : strategic marketing for people, planet and profit - Shams, S. M. Riad, 1979-; Brown, David M.; Hardcastle, Kimberley (Springer, 2025)
This core textbook empowers and inspires students with sustainable marketing strategies to pursue the triple bottom line; People, Planet and Profit. The purpose is to underpin a brand's commercial competitive advantage through its societal and environmental impact. It presents complex cross-disciplinary and cross-functional theoretical and practical discussions in a simplified manner to specify how the learning outcomes from different chapters can address the grand challenges associated with climate change, economic instability, geopolitical uncertainty, and inequity whilst underpinning profit-making ventures responsibly. The authors also demonstrate how the learning outcomes from this book can be applied in pursuit of each of the 17 United Nations (UN) Sustainable Development Goals (SDGs). Each chapter features a chapter summary, preliminary vignette, key terms, web exercises, review and discussion questions, and a practice quiz. Throughout the text there are also specific teaching features to provide students and instructors with an enhanced pedagogical experience. These features include: The Manager's Corner: These sections provide real-world examples that instructors may highlight to exemplify theory or as mini cases for discussion Sustainable Marketing in Action: These sections inspire students to apply concepts and theories to actual business situations This core textbook prepares the next generation of sustainable marketers to pursue their career goals with a commitment to fostering a positive and sustainable impact on society, the environment, the economy, their organizations, and themselves.
Keywords: Social responsibility of business.; Green marketing.; Marketing -- Social aspects.; elektronické knihy; electronic books